2016
DOI: 10.1063/1.4971453
|View full text |Cite
|
Sign up to set email alerts
|

Quantum effects in graphene monolayers: Path-integral simulations

Abstract: Path-integral molecular dynamics (PIMD) simulations have been carried out to study the influence of quantum dynamics of carbon atoms on the properties of a single graphene layer. Finitetemperature properties were analyzed in the range from 12 to 2000 K, by using the LCBOPII effective potential. To assess the magnitude of quantum effects in structural and thermodynamic properties of graphene, classical molecular dynamics simulations have been also performed. Particular emphasis has been laid on the atomic vibra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(132 citation statements)
references
References 84 publications
14
118
0
Order By: Relevance
“…17,60 Something similar has been proposed in recent years for crystalline membranes such as graphene. 33,47,61,62 For biological membranes, it was shown that values of the compressibility may appreciably differ when they are related to the real area A or in-plane area A p , and something analogous has been noticed recently for the elastic properties of graphene monolayers, as derived from classical molecular dynamics simulations. 47 The real area has been also called true, actual, or effective area in the literature.…”
Section: B Layer Areamentioning
confidence: 83%
“…17,60 Something similar has been proposed in recent years for crystalline membranes such as graphene. 33,47,61,62 For biological membranes, it was shown that values of the compressibility may appreciably differ when they are related to the real area A or in-plane area A p , and something analogous has been noticed recently for the elastic properties of graphene monolayers, as derived from classical molecular dynamics simulations. 47 The real area has been also called true, actual, or effective area in the literature.…”
Section: B Layer Areamentioning
confidence: 83%
“…Further simulation conditions are identical to those already described in our previous PIMD graphene simulations. 38,50…”
Section: Computational Conditionsmentioning
confidence: 99%
“…The systems considered here are of great practical interest and demonstrate pronounced NQE even at ambient conditions. 11,13,14 We note in passing that the system shown in Fig. 2 does not correspond to a stable state, although such a system plays an important role in the study of hydrogen isotope transport.…”
Section: Effective Temperatures For Nuclei or Collective Vibratimentioning
confidence: 99%
“…2,3 In liquid water, where the underlying tetrahedral network is primarily governed by the positions of the hydrogen atoms, it has been shown that accurate and reliable descriptions of the hydrogen bonding, [4][5][6] proton momentum distribution, 7 hydrated excess proton, 8,9 transport mechanism of aqueous hydroxide ions, 10 and numerous other phenomena 11 require a theoretical treatment of NQE beyond the harmonic approximation. In this regard, such non-classical nuclear behavior has also been observed in a number of systems throughout biology, chemistry, physics, and materials science, including DNA base pairs, 12 aromatic molecules, 13 graphene, 14,15 and equilibrium fractionation of stable aqueous Li isotopes, 16 to name a few.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation